Analysis Of The Factors Affecting Salesperson Performance In Chemspec Sdn Bhd. - Chan, Jacky Choon Cheong (2003)
Chemspec Sdn Bhd is in the business of manufacturing and distributing formulated chemicals to the metal fabricating industry. Currently, Chemspec is facing poor salesperson performance.Therefore, this case study is to identify the factors affecting the salesperson from performing.